Beam shaping with spatial light modulation - Duan, Ma Kyin May (2019)
Beam Shaping is a process of redistributing the irradiance and the phase of a beam of optical radiation. The phase of the beam is a major component that can determine the propagation properties of the beam profile. Many laser applications require a beam with irradiance distribution that specified or uniform over some cross-section of target profile in some plane. A Spatial Light Modulators (PO-LCSLM) is used in the technique of beam shaping as to modulate the beam properties, which can be used as a wave front sensor and compensator. Laser beam shaping technique using phase retrieval algorithm: Gerchburg-Saxton (GS), Generalized Adaptive-Additive (GAA), Weighted Gerchburg-Saxton (WGS) algorithms are used to shape the laser beam into arbitrary desired target shape in some plane. The computer-generated phase which is calculated based on algorithms are then retrieved and the programmable phase distribution is addressed to SLM to shape the input laser beam into uniform desired arbitrary shapes. The project results shown that the beam shaping technique can be realized into various shapes by both simulation and experimentally. The efficiency of algorithms are investigated for both simulated and experimented results.